MOOCs, Graduate Skills Gaps, and Employability: A Qualitative Systematic Review of the Literature - Santandreu Calonge, David; Aman Shah, Mariam (International Review of Research in Open and Distributed Learning, 2016)
The increasing costs of higher education (HE), growing numbers of flexible anytime, anywhere learners, and the prevalence of technology as a means to up-skill in a competitive job market, have brought to light a rising concern faced by graduate students and potential graduate employers. Specifically, there is a mismatch of useful skills obtained by students through HE institutions which is evident upon graduation. Faced with this dilemma, “graduate students,” or more specifically newly graduated students, with a with bachelor’s degree, and a growing number of employers are turning to Massive Open Online Courses, or MOOCs, as a complimentary mechanism through which this skills gap may be bridged. It is found in the literature that MOOCs are often discussed within the capacity of their development, their retention rates, institutional policies regarding their implementation, and other such related areas. Examinations into their broader uses, benefits, and potential pitfalls have been limited to date. Therefore, this paper aims to analyse the literature highlighting the use of MOOCs as a means to reduce the mismatch in graduate skills. As such, this literature analysis reviews the following relevant areas: higher education and graduate skills gap, today’s graduates and employability, and MOOCs and graduate skills. Through analysing the literature in these areas, this paper identifies gaps in the existing literature.